Piercing Law for Muslims in The Views of Al-Ghazali and Ibn Hajar Al-Haitami - Nabilah, Nafa; Thoha, Anis Malik; Fattah, Abdul; Haidar, Putri Bayu; Syari'ah, Atiris; Adib, Ahmad Hidhir (Program Studi Hukum Keluarga Islam, 2024)
This research aims to analyze the views of Islamic jurists on the use of piercing in a beautification context. The piercing phenomenon is widespread among Muslims, both men and women, in various Islamic countries. This research uses a qualitative type with a library research approach. This research methodology involves a comprehensive analysis of the views of various scholars and interpretations of verses from al-Qur’an, hadith, and fiqh books related to the topic of piercing in the context of religious law. From this research, the results showed that several scholars had different perspectives regarding this problem. Imam Ibnu Hajar al-Haitami considers piercing women's ears for jewelry purposes is permissible because it is part of 'urf (habit). However, al-Ghazali emphasized that piercing or self-harm and not permitted. There are prohibitions for men regarding piercing. Imam Ghazali and Ibn Hajar al-Haitami agree that nose piercing on women and men is forbidden because of the potential to cause painful wounds. Apart from that, making decorations in places other than ears is also prohibited because it can resemble the practices of infidels, wicked or immoral people. As a devout Muslim need to be careful and aware of the beautification jurisprudence so that it is under the principles and objectives of Islamic law.